2011
DOI: 10.3343/kjlm.2011.31.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Erythroleukemia Relapsing as Precursor B-cell Lymphoblastic Leukemia

Abstract: AML relapsing as ALL has rarely been reported. We describe the case of a 62-yr-old man who was diagnosed with erythroleukemia with a complex karyotype and achieved complete hematologic and cytogenetic remission after induction chemotherapy. However, 4 months after the initial diagnosis, he showed relapse with blasts showing a different morphology and immunophenotype and was diagnosed with precursor B-cell ALL. The relapsing precursor B-cell ALL presented with the same leukemic clones as the primary erythroleuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
0
14
1
Order By: Relevance
“…Similar case was reported as clonal rearrangements of the Ig heavy chain gene locus both in B cell ALL and subsequent AML cells [12]. The case of conversion from B cell lymphoblastic leukemia to erythroleukemia has complex karyotypic abnormalities in addition of original monosomy 5 and monosomy 7 [13]. chemotherapy could modify the original leukemic clone by amplifying or suppressing the differentiation programs, resulting in a lineage switch.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Similar case was reported as clonal rearrangements of the Ig heavy chain gene locus both in B cell ALL and subsequent AML cells [12]. The case of conversion from B cell lymphoblastic leukemia to erythroleukemia has complex karyotypic abnormalities in addition of original monosomy 5 and monosomy 7 [13]. chemotherapy could modify the original leukemic clone by amplifying or suppressing the differentiation programs, resulting in a lineage switch.…”
Section: Introductionmentioning
confidence: 80%
“…Cases of conversions from AML to ALL and vice versa are extremely rare [1][2][3][4][5][6][7][8][9][10][11][12][13]. Several hypotheses have been suggested to explain lineage conversion in leukemias, but the precise mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Conversions from AML to ALL occur less frequently, but have been reported for both children and adults ( Bernstein et al., 1986; Boeckx et al., 2004; Dorantes-Acosta et al., 2009; Emami et al., 1983; Krawczuk-Rybak et al., 2003; Lounici et al., 2000; Marcus et al., 1985; Rossi et al., 2012 ). Case reports of other types of leukemic conversions, such as erythroid leukemia into ALL, have also been published ( Park et al., 2011 ). In leukemic patients showing a relapse of a different lineage (so-called lineage switch), leukemic clones often have a different morphology, cell size, amount of cytoplasm, presence of Auer rods, and new phenotypic lineage markers ( Park et al., 2011; van den Ancker et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Complex karyotypes on presentation and relapse indicated that the ALL was from the same clone with the AML. [97] These collected reports showed rearrangement on 11q23 occurred on a high number of the cases.…”
Section: Study Casesmentioning
confidence: 99%
“…Among these 6 lineage switch cases, 5 cases were a conversion from ALL to AML, and 1 case was the reverse. In addition to its rare evidence, the reports [84,[86][87][88][89][90][91][92][93][94][95][96][97] also showed that the disease had a very poor prognosis with no standard treatment (most cases were resistant to chemotherapy at relapse). Conversion from ALL to AML forms the majority of cases and predominantly occurred in children.…”
Section: Study Casesmentioning
confidence: 99%